A retrospective study of thermal events on the mortality rate of hutch-reared dairy calves - Jurkovich, Viktor; Bakony, Mikolt; Reiczigel, Jeno (Frontiers in Veterinary Science, 2024)
Introduction Heat stress in hutch-reared dairy calves (Bos taurus) is highly relevant due to its adverse effects on animal welfare, health, growth, and economic outcomes. This study aimed to provide arguments for protecting calves against heat stress. It was hypothesized that the thermal stress caused by high ambient temperature in summer months negatively affects the survival rate in preweaning calves. Methods In a retrospective study, we investigated how calf mortality varied by calendar month and between thermoneutral and heat stress periods on a large-scale Hungarian dairy farm (data of 46,899 calves between 1991 and 2015). Results The daily mortality rate was higher in the summer (8.7–11.9 deaths per 10,000 calf days) and winter months (10.7–12.5 deaths per 10,000 calf-days) than in the spring (6.8–9.2 deaths per 10,000 calf-days) and autumn months (7.1–9.5 deaths per 10,000 calf-days). The distribution of calf deaths per calendar month differed between the 0–14-day and 15–60-day age groups. The mortality risk ratio was highest in July (6.92). The mortality risk in the 0–14-day age group was twice as high in periods with a daily mean temperature above 22°C than in periods with a daily mean of 5–18°C. Conclusions Heat stress abatement is advised in outdoor calf rearing when the mean daily temperature reaches 22°C, which, due to global warming, will be a common characteristic of summer weather in a continental region.